2014
DOI: 10.1161/circulationaha.114.010927
|View full text |Cite
|
Sign up to set email alerts
|

Response to Letter Regarding Article, “Lipoprotein(a) Concentrations, Rosuvastatin Therapy, and Residual Vascular Risk: An Analysis From the JUPITER Trial (Justification for the Use of Statins in Prevention: An Intervention Trial Evaluating Rosuvastatin)”

Abstract: We thank Dr Giral and colleagues for their comments on our recent study of lipoprotein(a) [Lp(a)].1 The quantitative assessment of Lp(a) has historically proven challenging in part because of the (1) highly heterogeneous number of Kringle-IV type-2 repeats (and thus molecular weight), and (2) lack of standardized methodology and calibration across published studies. A 2002 National Heart, Lung, and Blood Institute consensus workshop that recommended use of isoform size-independent assays that express Lp(a) con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
144
0
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(153 citation statements)
references
References 5 publications
4
144
0
5
Order By: Relevance
“…Analysis of data from the Justification for the Use of Statins in Prevention (JUPITER) trial did show a significant residual risk attributable to elevated Lp(a) in rosuvastatin-treated patients. 44 Thus, it appears reasonable at this time to consider the contribution of Lp(a) to a patient's risk even if the patient has existing disease and/or is receiving optimal lipid-lowering therapy.…”
Section: Elevated Plasma Lipoprotein(a) Concentrations As a Risk Factmentioning
confidence: 99%
See 1 more Smart Citation
“…Analysis of data from the Justification for the Use of Statins in Prevention (JUPITER) trial did show a significant residual risk attributable to elevated Lp(a) in rosuvastatin-treated patients. 44 Thus, it appears reasonable at this time to consider the contribution of Lp(a) to a patient's risk even if the patient has existing disease and/or is receiving optimal lipid-lowering therapy.…”
Section: Elevated Plasma Lipoprotein(a) Concentrations As a Risk Factmentioning
confidence: 99%
“…42 On the other hand, the large JUPITER trial found that a residual risk associated with elevated Lp(a) may persist in the background of low LDL levels resulting from aggressive statin therapy. 44 It must be emphasized that there have been no randomized clinical trials to date that have specifically addressed the question of whether monitoring Lp(a) concentrations or lowering Lp(a) therapeutically has a clinical benefit. Nonetheless, it seems prudent, given the existing evidence for Lp(a) as a causal risk factor, to measure Lp(a) in specific groups of patients and to tailor their clinical management accordingly.…”
Section: Koschinsky and Boffamentioning
confidence: 99%
“…36 Based on the JUPI-TER trial, the US Food and Drug Administration included asymptomatic JUPITER-eligible individuals with only 1 additional risk factor in the indications for rosuvastatin use. 37,38 The CRP was considered the most powerful inflammatory marker predicting CV events but also triggered considerable controversy. According to some subgroup analyses, some experts thought that the CV protective effect of statins was affected by the baseline CRP level.…”
Section: Discussionmentioning
confidence: 99%
“…Dr Alsulaimi collected the data. Dr El-Maouche drafted figures (1)(2). Dr Damluji drafted the article, and all authors critically revised it for important intellectual content and approved the final version to be submitted.…”
Section: Acknowledgmentmentioning
confidence: 99%
“…1 Having a similar structure to, but metabolically distinct function from the LDL particle, Lp(a) is an atherogenic lipoprotein that contains a liver-derived apolipoprotein(a) covalently bound to apolipoprotein B100 via a disulfide bond. 2,3 Among the proposed effects of apolipoprotein(a) that increase the risk of atherogenesis are (1) selective retention of Lp(a) within the arterial wall, (2) prothrombotic/anti-fibrinolytic effects secondary to structural resemblance with plasminogen and plasmin, but without fibrinolytic activity, and (3) promotion of smooth muscle cell migration and proliferation.…”
Section: Introductionmentioning
confidence: 99%